The Influence of Cash Position (CP) and Price Earning Ratio (PER) on Stock Prices at PT. Gudang Garam Tbk Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period - Puput Siti Robiatul Adawiyah; Endang Naryono (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine how stock prices are affected by Cash Position (CP) and Price Earning Ratio (PER). Associative quantitative research method. The data used in this study are secondary data from the financial statements of PT Gudang Garam Tbk. The purposive sampling method is used to collect samples. Construction and methods for analyzing data, classical assumption tests. Data are processed using Microsoft Excel and SPSS 26 programs. Panel data regression analysis, determination coefficient, and significance test of influence with t-test and F-test were carried out. The results of the analysis show that the correlation value of cash position to stock prices of -0.479 is included in the moderate category with a negative correlation direction. In addition, there is a correlation value between price earning ratio and stock price of 0.199. This value is included in the weak category with a positive correlation direction. The results of the study show that the price earning ratio variable does not affect stock prices, but cash position significantly affects stock prices. The results of the significance test of influence with the F test show that cash position and price earning ratio simultaneously have a large positive impact on stock prices. The analysis of the coefficient of determination (KD) that has been carried out shows that the independent variables, namely cash position and price earning ratio, have an influence of 32.5% on the dependent variable, namely stock price. Other variables not studied by the author contribute 67.5% of the remaining influence